2020
DOI: 10.1002/em.22366
|View full text |Cite
|
Sign up to set email alerts
|

Long INterspersed element‐1 mobility as a sensor of environmental stresses

Abstract: Long INterspersed element (LINE-1, L1) retrotransposons are the most abundant transposable elements in the human genome, constituting approximately 17%. They move by a "copy-paste" mechanism, involving reverse transcription of an RNA intermediate and insertion of its cDNA copy at a new site in the genome. L1 retrotransposition (L1-RTP) can cause insertional mutations, alter gene expression, transduce exons, and induce epigenetic dysregulation. L1-RTP is generally repressed; however, a number of observations co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 217 publications
(284 reference statements)
0
16
0
Order By: Relevance
“…Changes in the L1 methylation profile are often found in various forms of cancer [257,258,270,271]. Alcohol, smoking, and narcotic substances can cause a change in the methylation profile and L1 activation [265,[272][273][274][275][276][277]. The methylation profile can be changed in somatic tissues under influence of various exogenous and endogenous factors, including age-related changes or some diseases [278][279][280][281].…”
Section: L1 Regulation By Decreasing Chromatin Availability In Somatic Cellsmentioning
confidence: 99%
“…Changes in the L1 methylation profile are often found in various forms of cancer [257,258,270,271]. Alcohol, smoking, and narcotic substances can cause a change in the methylation profile and L1 activation [265,[272][273][274][275][276][277]. The methylation profile can be changed in somatic tissues under influence of various exogenous and endogenous factors, including age-related changes or some diseases [278][279][280][281].…”
Section: L1 Regulation By Decreasing Chromatin Availability In Somatic Cellsmentioning
confidence: 99%
“…To date, there is no direct demonstration of a causal relationship between exposure to a pollutant, TE mobility and development of a pathology. However, the arguments in favor of this hypothesis are of two types: (i) it has been shown experimentally or in population studies that pesticides and other environmental contaminants can modify the different levels of epigenetic regulation and thus create a context favorable to the mobility of TEs; (ii) mobility tests conducted on human or rodent cell models have shown that exposure to different contaminants or stresses can promote the mobility of TEs, in particular of LINE-1 elements [ 150 ].…”
Section: Role Of Stress and Environmental Pollution In Te Mobility An...mentioning
confidence: 99%
“…These approaches, which are still not widely used, are being developed and allow us to conclude that environmental pollutants have a strong impact on the activity of LINE-1 elements and, by extension, on all TEs. Thus, many pollutants have been tested for their ability to activate the mobility of LINE-1 elements in different human or animal cellular models [ 150 ]. It was found that metals such as aluminum, arsenic, cadmium, mercury and nickel cause an increase in LINE-1 retrotransposition events, whereas cobalt, lead, magnesium and zinc have no effect.…”
Section: Role Of Stress and Environmental Pollution In Te Mobility An...mentioning
confidence: 99%
“…The high worldwide seroprevalence of some of these viruses, such as that of HHV-1 and HHV-2 being around 90% (Wald and Corey, 2007), indicates that facilitating factors must exist that ultimately decide upon disease development. In consideration are comorbidities such as traumas to latently infected neurons (Zhang et al, 2013), immune-depriving conditions such as AIDS (Rodriguez et al, 2020), leukemia (Koskenvuo et al, 2008;Lancman et al, 2020), or stroke-induced immunodepression (Deroux et al, 2012;Hetze et al, 2013;Romer et al, 2015;Bertrand et al, 2019), and cumulative infectious burden (Sico et al, 2015), and also environmental factors (Liu et al, 2013;Brutting et al, 2018;Mueller et al, 2018;Del Re and Giorgi, 2020). The role of aging as a facilitating factor and the interplay with ERVs are discussed in detail below.…”
Section: Viral Infection Of the Central Nervous Systemmentioning
confidence: 99%